PENGARUH LATAR BELAKANG PENDIDIKAN GURU PAUD TERHADAP KINERJA GURU DI KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU - elytasari, Novi elytasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This study aimed to determine the effect Background Teacher Education Against Performance Teacher In Kecamatan Ujung Batu Kabupaten Rokan Hulu . In this study sample 30 teachers in the district stone rokan upstream end , the instruments used are interviews and observation , hypothesis of this study is the effect background educational teacher on the performance of teacher in kecamatan ujung batu kabupaten rokan hulu , It can be seen from the data obtained by the value of chi square calculation 112.29 % . This figure compared with the chi-square value in the table with 16 hp at the significant level of 5 % is obtained 26.296 % , was the result of the calculation is smaller than the chi square chi square results in the table ( 112.29 < 26 296 ) . That is the background of early childhood teacher education affects the performance of teachers Keywords : Background ECD Education Teacher , PerformanceTeacher